Cultivars and lines from ICARDA in spring durum wheat (Triticum durum Desf.) breeding in the Lower Volga region - S. N. Gaponov; G. I. Shutareva; N. M. Tsetva; I. S. Tsetva; I. V. Milovanov (Труды по прикладной ботанике, генетике и селекции)
Background. In 1991, under the cooperation agreement, the Federal Center of Agriculture Research (FCAR) of the South-East Region received the first improved accessions from the International Center for Agricultural Research in the Dry Areas (ICARDA). The objective of this work was to study the source material developed under comparable conditions of dryland agriculture and include the best accessions in scientific breeding programs.Material and methods. The presented data resulted from the study of spring durum wheat cultivars and lines from ICARDA (Aleppo, Syria), conducted in 1991–1998. Accessions with the best indicators of grain quality, adapted to the conditions of the Lower Volga, were selected and included into the crossing program. Grain analysis was carried out using the conventional methods for durum wheat as well as those modified by the Spring Durum Wheat Breeding Laboratory of the FCAR of the South-East.Result and conclusion. Many years of work led to identifying 22 lines of spring durum wheat, selected in the breeding nursery of the Main Competitive Trails (MCT) and in different years involved in complex multistep hybridization. The spring durum wheat cultivar ‘Lilek’ was included into the State Register for Selection Achievements in 2009, while cv. ‘Tamara’ was submitted to the State Variety Trials in 2020.